2016
DOI: 10.3329/bjp.v11i1.24163
|View full text |Cite
|
Sign up to set email alerts
|

Proposed mechanism of antibacterial mode of action of <i>Caesalpinia bonducella</i> seed oil against food-borne pathogens

Abstract: <p class="Abstract">The antibacterial mechanism of action of <em>Caesalpinia bonducella</em> seed oil on membrane permeability of <em>Listeria monocytogenes</em> NCIM 24563 (MIC: 2 mg/mL) and <em>Escherichia coli</em> ATCC 25922 (MIC: 4 mg/mL) was determined by measuring the extracellular ATP concentration, release of 260-nm absorbing materials, leakage of potassium ions and measurement of relative electrical conductivity of the bacterial cells treated at MIC concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Therefore, abnormalities to the structural integrity of cell membrane can detrimentally affect cell metabolism and lead to cell death. Some Eos was recognized to have membrane active properties against several microorganisms, causing leakage of cell constituents, including ions [24,25,26,27]. Thus, the overall results of the present study showed a remarkable increase in the leakage of ions.…”
Section: Measurement Of Potassium Ion Leakagesupporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, abnormalities to the structural integrity of cell membrane can detrimentally affect cell metabolism and lead to cell death. Some Eos was recognized to have membrane active properties against several microorganisms, causing leakage of cell constituents, including ions [24,25,26,27]. Thus, the overall results of the present study showed a remarkable increase in the leakage of ions.…”
Section: Measurement Of Potassium Ion Leakagesupporting
confidence: 54%
“…Further, the antibacterial effect may be also through derailment of proton motive force, regulating mitochondrial respiration, substrate oxidation, active transportation, and loss of pool biometabolites, as well as disruption of synthesis of macromolecules such as proteins, lipids and polysaccharides. In general, leakage of intracellular materials is induced by any antimicrobial agent results into the death of the cell [25]. The obtained activities may be attributed by the presence of several biologically active components present in the Eos of Pogostemon species.…”
Section: Measurement Of Potassium Ion Leakagementioning
confidence: 99%
“…Recently, the antibacterial activity of essential oils of Buddleja asiatica, Caesalpinia bonducella, Ginkgo biloba and Ligustrum lucidum are reported (Bajpai et al, 2015;Bajpai et al, 2016;Khan et al, 2015;Shukla et al, 2016). Previous studies showed that multiplication of pathogenic Salmonella spp., Escherichia coli (O157:H7), Listeria monocytogenes, Helicobacter pylori and Mycoplasma pneumoniae were inhibited by essential oils (Burt, 2004).…”
Section: Discussionmentioning
confidence: 99%